Community participation in formulating the post-2015 health and development goal agenda: reflections of a multi-country research collaboration - Brolan, Claire E.; Hussain, Sameera; Friedman, Eric A.; Ruano, Ana Lorena; Mulumba, Moses; Rusike, Itai; Beiersmann, Claudia; Hill, Peter S. (International journal for equity in health, 2014)
Global discussion on the post-2015 development goals, to replace the Millennium Development Goals when they expire on 31 December 2015, is well underway. While the Millennium Development Goals focused on redressing extreme poverty and its antecedents for people living in developing countries, the post-2015 agenda seeks to redress inequity worldwide, regardless of a country's development status. Furthermore, to rectify the UN's top-down approach toward the Millennium Development Goals' formulation, widespread negotiations are underway that seek to include the voices of people and communities from around the globe to ground each post-2015 development goal. This reflexive commentary, therefore, reports on the early methodological challenges the Go4Health research project experienced in its engagement with communities in nine countries in 2013. Led by four research hubs in Uganda, Bangladesh, Australia and Guatemala, the purpose of this engagement has been to ascertain a `snapshot' of the health needs and priorities of socially excluded populations particularly from the Global South. This is to inform Go4Health's advice to the European Commission on the post-2015 global goals for health and new governance frameworks. Five methodological challenges were subsequently identified from reflecting on the multidisciplinary, multiregional team's research practices so far: meanings and parameters around qualitative participatory research; representation of marginalization; generalizability of research findings; ethical research in project time frames; and issues related to informed consent. Strategies to overcome these methodological hurdles are also examined. The findings from the consultations represent the extraordinary diversity of marginal human experience requiring contextual analysis for universal framing of the post-2015 agenda. Unsurprisingly, methodological challenges will, and did, arise. We conclude by advocating for a discourse to emerge not only critically examining how and whose voices are being obtained at the community-level to inform the post-2015 health and development goal agenda, but also how these voices are being translated and integrated into post-2015 decision-making at national and global levels.